Variations in virulence factors, antifungal susceptibility and extracellular polymeric substance compositions of cryptic and uncommon Candida species from oral candidiasis - Orada Tosrisawatkasem; Sarut Thairat; Pairin Tonput; Pornpen Tantivitayakul (BMC Oral Health)
Abstract Background Infections caused by uncommon Candida spp. (species other than C. albicans, C. parapsilosis, C. glabrata, C. tropicalis, and C. krusei) have been continuously reported worldwide. However, virulence factors and antifungal susceptibility profiles of uncommon Candida species remain limited. This study aimed to investigate the extracellular hydrolytic enzyme activities, antifungal susceptibility in planktonic and biofilm forms of cryptic and uncommon Candida species as well as their biofilm structures and extracellular polymeric substance (EPS) compositions. Methods Candida species was identified by sequence analysis of the internal transcribed spacer (ITS) regions of ribosomal RNA. The phospholipase and proteinase activities were evaluated by agar plate method. Biofilm-forming activity was analyzed using XTT-metabolic assay. Antifungal susceptibility tests for fluconazole, voriconazole, 5-flucytosine, and caspofungin were performed with broth microdilution following the CLSI guideline. Candida biofilms were stained with fluorescent dyes for fungal cells (SYTO9), extracellular proteins (SYPRO Ruby), exopolysaccharides (Alexa Fluor 635-conjugated Concanavalin A) and analyzed using confocal laser scanning microscopy (CLSM). Results A total of 25 uncommon Candida isolates including C. metapsilosis, C. orthopsilosis, C. guilliermondii (new nomenclature: Meyerozyma guilliermondii), C. fermentati (Meyerozyma caribbica), C. lusitaniae (Clavispora lusitaniae), C. rugosa (Diutina rugosa), C. pararugosa and C. nivariensis (Nakaseomyces nivariensis ) were identified, with 8% and 40% of the oral Candida isolates producing phospholipase and proteinase, respectively. All Candida isolates in this study were susceptible to fluconazole, voriconazole, and 5-flucytosine whereas 2 C. rugosa isolates (8% of all tested isolates) reduce susceptibility to caspofungin. The antifungal concentrations required to inhibit biofilm (sMIC) of C. rugosa and C. guilliermondii complex were higher than those of other species. In addition, the C. rugosa and C. guilliermondii biofilms had relatively high quantities of proteins, exopolysaccharides, and extracellular DNA (eDNA) compared to other species. Significant positive correlations between eDNA and exopolysaccharides (r s = 0.77, p < 0.01) and proteins (r s = 0.60, p < 0.01) in Candida biofilms were observed. Conclusion Our results indicated variation in the expression of hydrolytic enzyme production and biofilm forming activities among uncommon Candida spp. All Candida isolates exhibited susceptibility to azole and 5-flucytosine. This study also presented the visualization of biofilm structures and distribution of EPS components in Candida biofilms.